1985
DOI: 10.1111/j.1600-079x.1985.tb00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrastructural Analysis of Differences in Exocytosis Number in Adrenomedullary Adrenaline Cells of Golden Hamsters Related to Time of Day, Pinealectomy, and Intracellular Region

Abstract: This research analyzed differences mainly in the incidence of exocytotic figures in adrenaline cells (A-cells) in pinealectomized (PX), sham-operated (SPX), and non-operated (NO) adult male golden hamsters, with the aim of determining whether these parameters change with the time of day and following pinealectomy, and whether intracellular regional differences exist in such changes. Animals acclimated to a standardized light:dark (LD) 12:12 photoperiod were sacrificed at 11 h after the onset of light (L-11h) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
(24 reference statements)
2
5
0
Order By: Relevance
“…Unique effects of sham operations like those reported by us in the adrenal medulla [Kachi et al, 1979[Kachi et al, , 1980a[Kachi et al, ,b, 1984[Kachi et al, , 1985a were also seen in the present study, especially evident as dampening of 24-h rhythmic changes in the nuclear size and as suppressive effects on the frequency of granulated nucleoli. Concerning the size of nuclei of the adrenomedullary cells, Weiss et al [ 19801 reported that lesions in the lateral hypothalamus or in the lateral mamillary nuclei resulted in a decrease in nuclear size.…”
Section: Effects Of Sham Operationssupporting
confidence: 85%
See 1 more Smart Citation
“…Unique effects of sham operations like those reported by us in the adrenal medulla [Kachi et al, 1979[Kachi et al, , 1980a[Kachi et al, ,b, 1984[Kachi et al, , 1985a were also seen in the present study, especially evident as dampening of 24-h rhythmic changes in the nuclear size and as suppressive effects on the frequency of granulated nucleoli. Concerning the size of nuclei of the adrenomedullary cells, Weiss et al [ 19801 reported that lesions in the lateral hypothalamus or in the lateral mamillary nuclei resulted in a decrease in nuclear size.…”
Section: Effects Of Sham Operationssupporting
confidence: 85%
“…We previously reported 24-h rhythmic changes in some quantitative morphological features of nucleoli in A-and N-cells, exocytosis in A-cells and nerve endings on A-and N-cells in Holtzman rats and Golden Hamsters and effects of pinealectomy and/or sham-operations on them [Kachi, 1983;Kachi et al, 1979Kachi et al, , 1980aKachi et al, ,b, 1984Kachi et al, , 1985a. In the present study, we further investigated quantitatively the nuclear-cytoplasmic (N/P) ratio, nuclear size, and the pars granulosa of the nucleolus of the adrenomedullary A-and Ncells, using the same specimens as used in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological evidence of exocytosis is difficult to capture in many endocrine and neuronal cells, because this process is probably very rapid and the granular contents may be immediately dispersed on their release. Many exocytotic figures have been reported in the adrenal chromaffin cells of the hamster, and convincing evidence of exocytosis has been demonstrated (Dinner 1967;Benedeczky and Somogyi 1975;Nagasawa 1977;Kachi et al 1985). This may reflect an unusual slowness of the process in the hamster, thereby allowing its detection by routine chemical procedures.…”
Section: Discussionmentioning
confidence: 89%
“…1967;Benedeczky and Somogyi. 1975;Nagasawa, 1977;Kachi et al, 1985]. We first observed the clear evidence of exocytosis in the PC 12 cells after 1-min exposure to a high concentration of potassium medium.…”
Section: Discussionmentioning
confidence: 99%